Reappraisal of the lithological units of the Wuguan Complex: implication for the Paleozoic evolution of the Qinling orogenic belt - Wang, Ge; Liao, Xiaoying; Liu, Liang; Wang, Yawei; Yang, Wenqiang (Frontiers in Earth Science, 2025)
The Wuguan Complex, located along the southern margin of the Shangdan suture zone, plays a critical role in investigating the tectonic evolution of the Qinling orogenic belt and constraining the collision timing between the North and South China Blocks. However, the age and provenance of lithological units within the Wuguan Complex, as well as its tectonic significance, remain subjects of ongoing debate. The U–Pb–Hf isotopic analysis of detrital zircons from the meta-sedimentary rocks of the Wuguan Complex reveals distinctly different age patterns and depositional ages, which can be subdivided into a Devonian (ca. 380–400 Ma) unit and a Mid-Neoproterozoic (732–743 Ma) unit. The Devonian unit has a detrital age spectrum with two main peaks at ∼440 and ∼893 Ma, interpreted to reflect a mixed source derived from the early Paleozoic North Qinling magmatic arc and the Neoproterozoic South Qinling basement, corresponding to the Devonian Liuling Group in the South Qinling. The Mid-Neoproterozoic unit has an age spectrum with a dominant peak at ∼898 Ma, interpreted to be primarily derived from widespread Neoproterozoic South Qinling volcanic and plutonic rocks. The meta-mafic volcanic rocks in the Wuguan Complex have a mean weighted zircon U–Pb age of 436 ± 6 Ma, exhibit high TiO2 contents with both E-MORB and OIB affinities, and show depleted zircon εHf(t) values, indicating formation within an intraplate tectonic setting. Combining these findings with previous data, we propose a reappraisal of the lithological units in the Wuguan Complex, which includes (1) the Mid-Neoproterozoic (ca. 732–743 Ma) sedimentary unit developed on the ancient South Qinling basement (2) the Silurian (ca. 430–440 Ma), meta-mafic volcanic unit, indicative of a local tectonic transition in the South Qinling belt from compressional to extensional during the Silurian, and (3) the Devonian (ca. 380–400 Ma) sedimentary unit, correlative with the Devonian Liuling Group, which was deposited during the final stages of closure of the Paleo-Qinling Ocean. These units were structurally juxtaposed by ductile strike-slip faults during the Early Carboniferous.